Synthesis of 5-unsubstituted dihydropyrimidinone-4-carboxylates from deep eutectic mixtures - Gore, Sangram; Baskaran, Sundarababu; König, Burkhard (Beilstein Journal of Organic Chemistry, 2022)
A facile one-pot synthesis of 5-unsubstituted dihydropyrimidinones from β,γ-unsaturated ketoesters in low melting ʟ-(+)-tartaric acid–N,N-dimethylurea mixtures is reported. This solvent-free method is very general and provides easy access to 5-unsubstituted dihydropyrimidinone-4-carboxylate derivatives in good yields.
Keywords: green protocol; mild conditions; no additional catalyst; solvent free; triple role of melt

(untitled) - Biginelli, P. (Gazz. Chim. Ital., 1893)

(untitled) - Matos, L. H. S.; Masson, F. T.; Simeoni, L. A.; Homem-de-Mello, M. (Eur. J. Med. Chem., 2018)

(untitled) - Ismaili, L.; Monnin, J.; Etievant, A.; Arribas, R. L.; Viejo, L.; Refouvelet, B.; Soukup, O.; Janockova, J.; Hepnarova, V.; Korabecny, J.; Kucera, T.; Jun, D.; et al. (ACS Chem. Neurosci., 2021)

(untitled) - Li, Y.; Tan, T.; Zhao, Y.; Wei, Y.; Wang, D.; Chen, R.; Tao, L. (ACS Macro Lett., 2020)

(untitled) - Atwal, K. S.; Rovnyak, G. C.; Schwartz, J.; Moreland, S.; Hedberg, A.; Gougoutas, J. Z.; Malley, M. F.; Floyd, D. M. (J. Med. Chem., 1990)

(untitled) - Atwal, K. S.; Rovnyak, G. C.; Kimball, S. D.; Floyd, D. M.; Moreland, S.; Swanson, B. N.; Gougoutas, J. Z.; Schwartz, J.; Smillie, K. M.; Malley, M. F. (J. Med. Chem., 1990)

(untitled) - Cho, H.; Ueda, M.; Shima, K.; Mizuno, A.; Hayashimatsu, M.; Ohnaka, Y.; Takeuchi, Y.; Hamaguchi, M.; Aisaka, K.; Hidaka, T.; Kawai, M.; Takeda, M.; et al. (J. Med. Chem., 1989)

(untitled) - Barrow, J. C.; Nantermet, P. G.; Selnick, H. G.; Glass, K. L.; Rittle, K. E.; Gilbert, K. F.; Steele, T. G.; Homnick, C. F.; Freidinger, R. M.; Ransom, R. W.; Kling, P.; Reiss, D.; et al. (J. Med. Chem., 2000)

(untitled) - Jain, K. S.; Bariwal, J. B.; Kathiravan, M. K.; Phoujdar, M. S.; Sahne, R. S.; Chauhan, B. S.; Shah, A. K.; Yadav, M. R. (Bioorg. Med. Chem., 2008)

(untitled) - Atwal, K. S.; Swanson, B. N.; Unger, S. E.; Floyd, D. M.; Moreland, S.; Hedberg, A.; O'Reilly, B. C. (J. Med. Chem., 1991)

(untitled) - Rovnyak, G. C.; Atwal, K. S.; Hedberg, A.; Kimball, S. D.; Moreland, S.; Gougoutas, J. Z.; O'Reilly, B. C.; Schwartz, J.; Malley, M. F. (J. Med. Chem., 1992)

(untitled) - Grover, G. J.; Dzwonczyk, S.; McMullen, D. M.; Normandin, D. E.; Parham, C. S.; Sleph, P. G.; Moreland, S. (J. Cardiovasc. Pharmacol., 1995)

(untitled) - Farghaly, A. M.; AboulWafa, O. M.; Elshaier, Y. A. M.; Badawi, W. A.; Haridy, H. H.; Mubarak, H. A. E. (Med. Chem. Res., 2019)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Zhou, M.; Wang, Y.; Lin, X.; Wan, J.; Wen, C. (Front. Pharmacol., 2021)

(untitled) - Mayer, T. U.; Kapoor, T. M.; Haggarty, S. J.; King, R. W.; Schreiber, S. L.; Mitchison, T. J. (Science, 1999)

(untitled) - Kong, K.-H.; Chen, Y.; Ma, X.; Chui, W. K.; Lam, Y. (J. Comb. Chem., 2004)

(untitled) - Summa, V.; Petrocchi, A.; Bonelli, F.; Crescenzi, B.; Donghi, M.; Ferrara, M.; Fiore, F.; Gardelli, C.; Gonzalez Paz, O.; Hazuda, D. J.; Jones, P.; Kinzel, O.; et al. (J. Med. Chem., 2008)

(untitled) - Oh, S.; Park, Y.; Engelhart, C. A.; Wallach, J. B.; Schnappinger, D.; Arora, K.; Manikkam, M.; Gac, B.; Wang, H.; Murgolo, N.; Olsen, D. B.; Goodwin, M.; et al. (J. Med. Chem., 2018)

(untitled) - Wang, Z.-T.; Xu, L.-W.; Xia, C.-G.; Wang, H.-Q. (Tetrahedron Lett., 2004)

(untitled) - Ren, Y.-M.; Cai, C. (Monatsh. Chem., 2009)

(untitled) - Steele, T. G.; Coburn, C. A.; Patane, M. A.; Bock, M. G. (Tetrahedron Lett., 1998)

(untitled) - Bussolari, J. C.; McDonnell, P. A. (J. Org. Chem., 2000)

(untitled) - Fang, Z.; Lam, Y. (Tetrahedron, 2011)

(untitled) - Kambappa, V.; Kotturappa, C. G.; Manjunath, R. S.; Shivaramu, P. D. (J. Heterocycl. Chem., 2020)

(untitled) - Sabitha, G.; Reddy, K. B.; Srinivas, R.; Yadav, J. S. (Helv. Chim. Acta, 2005)

(untitled) - Gore, S.; Baskaran, S.; Koenig, B. (Green Chem., 2011)

(untitled) - Abbott, A. P.; Boothby, D.; Capper, G.; Davies, D. L.; Rasheed, R. K. (J. Am. Chem. Soc., 2004)

(untitled) - Carriazo, D.; Serrano, M. C.; Gutiérrez, M. C.; Ferrer, M. L.; del Monte, F. (Chem. Soc. Rev., 2012)

(untitled) - Zhang, Q.; De Oliveira Vigier, K.; Royer, S.; Jérôme, F. (Chem. Soc. Rev., 2012)

(untitled) - Ruß, C.; König, B. (Green Chem., 2012)

(untitled) - Imperato, G.; Eibler, E.; Niedermaier, J.; König, B. (Chem. Commun., 2005)

(untitled) - Imperato, G.; Höger, S.; Lenoir, D.; König, B. (Green Chem., 2006)

(untitled) - Ilgen, F.; König, B. (Green Chem., 2009)

(untitled) - Imperato, G.; Vasold, R.; König, B. (Adv. Synth. Catal., 2006)

(untitled) - Ruß, C.; Ilgen, F.; Reil, C.; Luff, C.; Haji Begli, A.; König, B. (Green Chem., 2011)

(untitled) - Gore, S.; Baskaran, S.; Koenig, B. (Adv. Synth. Catal., 2012)

(untitled) - Gore, S.; Baskaran, S.; König, B. (Org. Lett., 2012)

(untitled) - Gore, S.; Chinthapally, K.; Baskaran, S.; König, B. (Chem. Commun., 2013)

(untitled) - Stecher, E. D.; Incorvia, M. J.; Kerben, B.; Lavine, D.; Oen, M.; Suhl, E. (J. Org. Chem., 1973)